A Strategy to Prepare Primary Care Clinicians for Discussing Stopping Cancer Screening With Adults Older Than 75 Years. Issue 4 (7th July 2020) - Schonberg, Mara A; Karamourtopoulos, Maria; Jacobson, Alicia R; Aliberti, Gianna M; Pinheiro, Adlin; Smith, Alexander K; Davis, Roger B; Schuttner, Linnaea C; Hamel, Mary Beth
Abstract: Background and Objectives: Adults older than 75 years are overscreened for cancer, especially those with less than 10-year life expectancy. This study aimed to learn the effects of providing primary care providers (PCPs) with scripts for discussing stopping mammography and colorectal cancer (CRC) screening and with information on patient's 10-year life expectancy on their patients' intentions to be screened for these cancers. Research Design and Methods: Patient participants, identified via PCP appointment logs, completed a questionnaire pre- and postvisit. Primary care providers were given scripts for discussing stopping screening and information on patient's 10-year life expectancy before these visits. Primary care providers completed a questionnaire at the end of the study. Patients and PCPs were asked about discussing stopping cancer screening and patient life expectancy. Patient screening intentions (1–15 Likert scale; lower scores suggest lower intentions) were compared pre- and postvisit using the Wilcoxon signed-rank test. Results: Ninety patients older than 75 years (47% of eligible patients reached by phone) from 45 PCPs participated. Patient mean age was 80.0 years ( SD = 2.9), 43 (48%) were female, and mean life expectancy was 9.7 years ( SD = 2.4). Thirty-seven PCPs (12 community-based) completed a questionnaire. Primary care providers found the scripts helpful (32 [89%]) and thought they would use them frequently (29 [81%]). Primary care providers also found patient life expectancy information helpful (35 [97%]). However, only 8 PCPs (22%) reported feeling comfortable discussing patient life expectancy. Patients' intentions to undergo CRC screening (9.0 [ SD = 5.3] to 6.5 [ SD = 6.0], p < .0001) and mammography screening (12.9 [ SD = 3.0] to 11.7 [ SD = 4.9], p = .08) decreased from pre- to postvisit (significantly for CRC). Sixty-three percent of patients (54/86) were interested in discussing life expectancy with their PCP previsit and 56% (47/84) postvisit. Discussion and Implications: PCPs found scripts for discussing stopping cancer screening and information on patient life expectancy helpful. Possibly, as a result, their patients older than 75 years had lower intentions of being screened for CRC. Clinical Trials Registration Number: NCT03480282